Active transpressional tectonics in the Andean forearc of southern Peru quantified by 10Be surface exposure dating of an active fault scarp - Benavente C. (2017)
Our understanding of the style and rate of Quaternary tectonic deformation in the forearc of the Central Andes is hampered by a lack of field observations and constraints on neotectonic structures. Here we present a detailed analysis of the Purgatorio fault, a recently recognized active fault located in the forearc of southern Peru. Based on field and remote sensing analysis (Pléiades DEM), we define the Purgatorio fault as a subvertical structure trending NW-SE to W-E along its 60 km length, connecting, on its eastern end, to the crustal Incapuquio Fault System. The Purgatorio fault accommodates right-lateral transpressional deformation, as shown by the numerous lateral and vertical plurimetric offsets recorded along strike. In particular, scarp with a 5 m cumulative throw is preserved and displays cobbles that are cut and covered by slickensides. Cosmogenic radionuclide exposure dating (10Be) of quartzite cobbles along the vertical fault scarp yields young exposure ages that can be bracketed between 0 to 6 ka, depending on the inheritance model that is applied. Our preferred scenario, which takes in account our geomorphic observations, implies at least two distinct rupture events, each associated with ~3 and ~2 m of vertical offset. These two events plausibly occurred during the last thousand years. Nevertheless, an interpretation invoking more tectonic events along the fault cannot be ruled out. This work affirms crustal deformation along active faults in the Andean forearc of southern Peru during the last thousand years. ©2017. American Geophysical Union. All Rights Reserved.